Thiazolidinediones: Synthesis of Some New 5-(ω-carboxy propyl/pentyl)-2,4-thiazolidinedione and 3-substituted phenyl-5-( ω-carboxy propyl/pentyl)-2,4-thiazolidinediones. - SOLANKEE, ANJANI; KAPADIA., KISHOR (Asian Journal of Chemistry, 2010)
3-Substituted phenyl-5-(ω-carboxy propyl/pentyl) 2,4-thiazolidinediones and 5-(ω-carboxy propyl/pentyl) 2,4-thiazolidinediones have been prepared from 2-phenyl imino-3-substituted phenyl-5-(ω-carboxy propyl/pentyl)-4-thiazolidinone and 2-phenyl imino-5-(ω-carboxy propyl/pentyl)-4-thiazolidinones, prepared by the condensation of 2-bromo adipic/suberic acid and thioureas, by the treatment of hydrochloric acid.